2020
DOI: 10.1183/13993003.02355-2019
|View full text |Cite
|
Sign up to set email alerts
|

New method for rapid and dynamic quantification of elastase activity on sputum neutrophils from patients with cystic fibrosis using flow cytometry

Abstract: Small molecule FRET flow cytometry is a new method that enables rapid and sensitive quantification of surface-bound elastase activity on sputum neutrophils from patients with cystic fibrosis and potentially other neutrophilic airway diseases http://bit.ly/2IegeSB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…It is also worth noting that, as has been mentioned, some proteases, including NE, cathepsin G and MMP-12, are not exclusively present as free soluble forms [ 100 , 157 , 158 ], and as such, can be shielded from their inhibitors by remaining membrane-associated or complexed with extracellular molecules [ 91 , 159 ]. Shielded protease localisations are increasingly being recognised in CLDs and assessing these inaccessible forms by, for example, fluorescence resonance energy transfer (FRET)-based assays [ 160 , 161 ], may bring to light a more substantial protease burden than has been appreciated to date, as well as providing more effective targeting strategies for pharmacological inhibitors.…”
Section: Proteases and Mucosal Immunitymentioning
confidence: 99%
“…It is also worth noting that, as has been mentioned, some proteases, including NE, cathepsin G and MMP-12, are not exclusively present as free soluble forms [ 100 , 157 , 158 ], and as such, can be shielded from their inhibitors by remaining membrane-associated or complexed with extracellular molecules [ 91 , 159 ]. Shielded protease localisations are increasingly being recognised in CLDs and assessing these inaccessible forms by, for example, fluorescence resonance energy transfer (FRET)-based assays [ 160 , 161 ], may bring to light a more substantial protease burden than has been appreciated to date, as well as providing more effective targeting strategies for pharmacological inhibitors.…”
Section: Proteases and Mucosal Immunitymentioning
confidence: 99%
“…This donor/acceptor combination ensured stable readouts and found wide applicability in the past, from flow cytometry to intravital two-photon confocal microscopy. 25,34 After protease addition to a solution containing H-NE and H-CG, respectively, we observed a strong increase in donor fluorescence, indicating cleavage of the reporters and loss of FRET (Figure 1c and Figure S21b). The ratio between the fluorescence signal recorded at the donor and acceptor λ max was used as an indicator of protease activity (Figure S21b, S21c).…”
mentioning
confidence: 98%
“…Remarkably, NET’s multifaceted functional properties originate from the immunological activity of their associated enzymes: ,, neutrophil elastase (NE) and cathepsin G (CG) are neutrophil serine proteases (NSPs), well-known perpetuators of inflammation and promising prognostic biomarkers. The use of protease activity reporters as anti-inflammatory treatment indicators for airway diseases is spreading. Importantly, once secreted, NE and CG tether to the plasma membrane, where they act undisturbed by antiproteases, as well as to extracellular DNA webs . During NETosis, NE acts intra- and extracellularly.…”
mentioning
confidence: 99%
“…Weber et al, reported the results for 27 patients with TGLP. Accordingly, 14 individuals underwent laryngeal suspension with stitches between the hyoid bone and mandible, and 18 cases underwent palatal prosthesis augmentation [19]. It is reasonable to believe that the palatal augmentation allows the contact between the reconstructive flap and the soft palate, justifying the good swallowing results reported by the author.…”
Section: Figure 4: Different Options For Reconstructive Flap Positioningmentioning
confidence: 97%